Intensification of emotional needs in women with ovarian tumours and uterine fibroids - Pawłowska, Beata; Międlar, Krzysztof; Biały-Międlar, Karolina Biały-Międlar; Lekan, Monika; Fijałkowska, Paula; Landman, Marta (Current Problems of Psychiatry, 2012)
The objective of the study was to answer the question: do any dependencies occur, if any, as regards the intensification of emotional needs in women with ovarian tumours and uterine fibroids and in healthy women? The examined group consisted of 60 patients qualified for surgery due to benign ovarian tumours (30 women) and uterine fibroids (30 women) as well as 30 healthy women. The average age of patients was 40 years. The following research methods were used in the work: The Assessment of Psychological Needs Questionnaire by Murray and the Socio-demographic Questionnaire designed by the authors. Results and conclusions: • As compared to healthy women, the patients with ovarian tumours and uterine fibroids are characterised by significantly more intensified need for succorance – seeking support, care, aid, comfort, tenderness, possibility of telling about their problems, suffering and worries. • As compared to the women with ovarian tumours, the patients with uterine fibroids are characterised by a significantly more intensified sensitivity, conformity, susceptibility to suggestion, willingness to co-operate, need for establishing interpersonal relationships, co-operation, trust in other people and intensified need for succorance. • As compared to healthy women, the patients with uterine fibroids show a significantly more intensified need for succorance, need for getting privileges, greater conformity, submissiveness, willingness to co-operate, to avoid conflicts, to rely on others, need for affiliation (establishing emotional ties with other people) and need for sympathy, self-pity, getting feel of own suffering and concentrating on the damage to their bodies. • No significant differences were found between the women with ovarian tumours and healthy women.